2009
DOI: 10.1358/dot.2009.45.5.1371116
|View full text |Cite
|
Sign up to set email alerts
|

Empiric antibiotic selection for infectious emergencies: Bacterial pneumonia, meningitis and sepsis

Abstract: Appropriate early management of infectious emergencies is essential to preventing adverse outcomes. Clinicians in acute-care settings must be prepared to provide appropriate empiric antibiotics, as failure to do so has been associated with an increased risk of mortality. Empiric treatment of these infections requires knowledge of the disease state, most common pathogens, and patient-specific risk factors. Additionally, regional and institutional patterns of antibiotic resistance must be taken into consideratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…More and more materials in the medical fields are expected to have excellent antimicrobial capability because bacterial infection can cause severe safety issues, such as pneumonia, meningitis, and sepsis. ,, Here, Escherichia coli and Staphylococcus aureus were selected as representatives of Gram-negative and Gram-positive bacteria to determine the antimicrobial ability of different concentrations of protein MP-KE. As illustrated in Figure a, the control plates were covered with dense E.…”
Section: Resultsmentioning
confidence: 99%
“…More and more materials in the medical fields are expected to have excellent antimicrobial capability because bacterial infection can cause severe safety issues, such as pneumonia, meningitis, and sepsis. ,, Here, Escherichia coli and Staphylococcus aureus were selected as representatives of Gram-negative and Gram-positive bacteria to determine the antimicrobial ability of different concentrations of protein MP-KE. As illustrated in Figure a, the control plates were covered with dense E.…”
Section: Resultsmentioning
confidence: 99%
“…The therapeutic goal is to initiate antibiotic therapy within 60 minutes of a patient’s arrival in the emergency room. In patients suspected of having bacterial meningitis, cerebrospinal fluid (CSF) should be obtained for cultures and empirical antimicrobial therapy initiated without delay [2,3]. Diagnosis of bacterial meningitis is confirmed by CSF culture the “gold standard” for diagnosis of meningitis and it is equally important to obtain the antimicrobial susceptibility of the causative microorganism to rationalize treatment [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Malnutrition is one of the risk factors that can expose to the development of meningitis [6]. This study indicated that about 21% of the patients were malnourished.…”
Section: Discussionmentioning
confidence: 77%
“…The therapeutic goal is to initiate antibiotic therapy within 60 minutes of patient arrival in the emergency room. In patients suspected of having bacterial meningitis, CSF should be obtained for cultures and empirically antimicrobial therapy should be initiated without delay [5,6].…”
Section: Introductionmentioning
confidence: 99%